The Role of Music Pedagogy in the Effective Teaching of Music in the 5th-7th Grade of General Secondary School - Abdumutalibovich, Ma’rufjon Ashurov (Jurnal Pendidikan Non formal, 2024)
This article is based on the results of the pilot test of the dissertation, in which the role of music pedagogy in the effective teaching of music in 5-7 grades of general secondary schools is highlighted. The methodology encompasses a blend of descriptive, categorical, declarative, and instructive approaches. This paper will examine key aspects of music pedagogy, the basic principles of music teaching, and methods and techniques that will help create effective and interesting music teaching.